SELECTION OF AMMONIA AND TSS REMOVAL IN EFFLUENT WATER FROM DURI KOSAMBI IPLT USING ANALYTIC HIERARCHY PROCESS (AHP) - Farhan Muhammad Hilmi; Reifaldy Tsany Betta Aryanto; Sri Dewi Handayani; Yesaya Emeraldy Priutama; Intan Rahmalia; Evi Siti Sofiyah; Ariyanti Sarwono; I Wayan Koko Suryawan (Prodi Magister Teknik Sipil Unsyiah, 2022)
The ammonia and total suspended solids (TSS) content in the wastewater of IPLT Duri Kosambi Jakarta City still does not meet the standard. It requires further processing that needs to be applied. The three treatments that are used as alternatives are GAC Adsorption, Zeolite Adsorption, and Built-Up Wetlands. The purpose of this study is to analyze the best alternative suitable for use as advanced processing in IPLT DuriKosambi with analysis of decision-making analysis. Analysis decision-making is carried out using the analytical hierarchy process (AHP) using four criteria: construction costs, TSS removal efficiency, ammonia removal efficiency, and Human Resources (HR) requirements. The highest scores of the GAC Adsorption, Zeolite Adsorption, and Constructed Wetland alternatives were 0.41; 0.30l, and 0.28. So that the GAC unit is the unit selected based on the criteria set in the AHP criteria.